INNOVATIVE TECHNOLOGIES IN THE PRODUCTION OF SEWING PRODUCTS: CUTTING PRODUCTION - RUBANKA, Mykola; DVORZHAK, Volodymyr; RUBANKA, Alla; POLISHCHUK, Oleh; HORIASHCHENKO, Serhiy (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article considers the technological process of production of the cutting department of a sewing enterprise and the typical equipment used during such a process. It is revealed that the increase in the range of sewing products, the appearance of new materials, the speed of changing models, methods of processing, etc., necessitates a systematic search for rational and effective solutions for the technological process of production, including through the introduction of modern innovative equipment. The most used standard equipment of the cutting department of a sewing enterprise has been analyzed. The main requirements for the equipment involved in the technological process of production of the cutting department of a sewing enterprise have been determined. Also, the ways of possible improvement of the cutting department of a sewing enterprise have been outlined. The object of the research is a typical cutting department of a Ukrainian sewing enterprise, i.e. the technological process of production and the equipment used during such process. The method of system analysis is used. Theoretical studies are based on the main provisions of light industry production technologies. A generalized classification scheme of the standard equipment of the cutting department of a sewing enterprise has been developed, which can be used at light industry enterprises, in particular the cutting department of a sewing enterprise, when choosing energy-efficient and high-tech equipment. Also, the main problems that need to be solved for the successful development of an average sewing enterprise are outlined. The results of the study can be used in the design of new and modernization of existing cutting departments of sewing enterprises.
Keywords: technological process; cutting department; sewing enterprise; cutting production equipment; cutting; sewing materials